Enhancing Early Childhood Financial Literacy Through FinSOLEkid Indonesia: A Comparative Study of Digital Platforms - Fitriah, Nurlaeli; Degeng, Made Duananda Kartika; Degeng, I Nyoman Sudana; Praherdhiono, Henry (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2023)
This study investigates the impact of FinSOLEkid Indonesia, a game-based educational application, on financial literacy among early childhood learners aged 5-6 years. Utilizing a quasi-experimental design with two experimental groups, one using a PC version and the other an Android version, the study aims to determine the effectiveness of digital platforms in enhancing financial understanding. Subjects were chosen through purposive sampling based on their interaction with money, comprehension of in-game instructions, and ability to use digital devices. Data collection involved multiple-choice tests tailored with game elements and visual aids to suit the developmental stage of the participants. The analysis, conducted using the Kruskal-Wallis test and N-Gain scores, revealed that the PC version of FinSOLEkid Indonesia was more effective in augmenting financial knowledge than its Android counterpart and conventional methods. However, the suitability of the application for children under the age of 5-6 remains questionable due to the presence of written instructions. The study highlights the importance of selecting appropriate educational media and content for early childhood. It suggests that such technology-enhanced learning tools, while effective, need to be tailored to the developmental needs of the learners. These findings offer insights into the potential of digital learning platforms in early childhood education, emphasizing the need for age-appropriate design and content in educational technology.